The sisters of Sea View [large type] - Klassen, Julie, 1964- (Klassen, Julie, 1964- On Devonshire shores, 2023)
"When their father's death leaves them impoverished, Sarah Summers convinces her sisters to open their seaside home to guests to provide for their ailing mother. Emily and Georgiana agree, but Viola, who wears a veil to cover a scar, detests the idea. Determined to stay together, the sisters begin the new venture. Instead of the elderly invalids they expect, however, they find themselves hosting eligible gentlemen. Sarah is torn between a growing attraction to a mysterious Scottish widower and duty to her family. Meanwhile, the new situation exposes Viola's scars--both the visible and those hidden deep within--and her cloistered heart will never be the same"--